Exploring Challenges of Working Sandwiched Mothers and Organization Support - Choo, Chun Yenn; Zaiton, Hassan; Mark, Kasa; Mohd Firdaus, Zakaria; Victoria, Jonathan (Human Resource Management Academic Research Society, 2024)
The multigenerational commitments and obligations of working mothers who are sandwiched between caring for their children and elderly family members jeopardize their ability to maintain role balance. Previous research on the topic, particularly in a Malaysian context, is limited. This qualitative study aims to address this gap by examining the challenges faced by seven working sandwiched mothers in Malaysia and the social support provided by organizations as they navigate multiple roles as caregivers, spouses, parents, and employees. Specifically, the study investigates (1) how these women manage their combined responsibilities and (2) what types of organizational support are available to them. Drawing on Conservation of Resources theory which emphasizes protecting one's resources from depletion or loss; we found that emotional stress, work-induced stress, and financial constraints pose significant challenges for these individuals. Although flexibility is crucial for managing competing demands effectively, our findings suggest that organizations do not offer enough support in this regard. Overall, our study illuminates the experiences of working sandwiched mothers facing complex role conflicts while highlighting the need for workplace policies that prioritize